The Soft Skill Model Based On Emotional Intelligence In Taruna Polytechnic of Shipping Science Semarang - Yuar Ningga, Sintha; Rusdarti, Rusdarti; Suminar, Tri (Educational Management, 2019)
Learning soft skills as part of efforts to establish a professional attitude. Soft skills are skills that is done by non-technical, that is not shaped or invisible form. These soft skills can be regarded as personal and inter-personal skills at cadets in PIP Semarang to develop theirself in the course of work or activities. This study aims to (1) analyze the impact of character education and parenting on emotional intelligence (2) analyze the impact of character education and upbringing of the soft skills through emotional intelligence (3) analyze the effect of the soft skills towards emotional intelligence on Politektik Youth Sailing Science Semarang. This study is used a quantitative approach, the entire study population cadets PIP Semarang numbering 1. 189 cadets. The sample size is 175 cadets of PIP Semarang. The data used are primary data, the data captured by the questionnaire that has been tested for validity and reliability. Analysis of data using path analysis and Sobel test to determine mediasi.Hasil variables showed that (1) the impact of character education and parenting on emotional intelligence was positively and significantly, with Sig 0.000 <0.05, (2) the impact of character education and parenting against the soft skills through emotional intelligence, either directly or indirectly is positive and significant, (3) the effect of the soft skills of emotional intelligence by 20.43%, a positive and significant effect on PIP Semarang.